2009
DOI: 10.4110/in.2009.9.6.255
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cordycepin and Adenosine on the Phenotypic Switch of Macrophages via Induced Anti-inflammatory Cytokines

Abstract: BackgroundChronic low grade inflammation is closely linked to type II diabetes, obesity, and atherosclerosis. Macrophages play a key role in the regulation of pro- or anti-inflammatory actions at the lesion sites of disease. Components of cordyceps militaris, cordycepin and adenosine, have been used for the modulation of inflammatory diseases. The effects of cordycepin in the modulation of macrophages have yet to be elucidated. We investigated the effects of cordycepin and adenosine on the morphological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…In our DSS-induced acute colitis models, CM extract not only suppressed colonic infiltration of inflammatory cells, but also inhibited intestinal expression of pro-inflammatory cytokines, such as IL-1 and TNF-␣. As reported in a previous study, agents capable of blocking inflammatory cascades have potential in prevention and treatment of IBD (Barrie and Regueiro, 2007).Several groups demonstrated that Cordyceps militaris comprised of numerous components including cordycepin (Kim et al, 2006), adenosine (Shin et al, 2009), and polysaccharide (Yu et al, 2004), which have anti-inflammatory activities. Further studies will explore the effect of active components including cordycepin in Cordyceps militaris in acute colitis model.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our DSS-induced acute colitis models, CM extract not only suppressed colonic infiltration of inflammatory cells, but also inhibited intestinal expression of pro-inflammatory cytokines, such as IL-1 and TNF-␣. As reported in a previous study, agents capable of blocking inflammatory cascades have potential in prevention and treatment of IBD (Barrie and Regueiro, 2007).Several groups demonstrated that Cordyceps militaris comprised of numerous components including cordycepin (Kim et al, 2006), adenosine (Shin et al, 2009), and polysaccharide (Yu et al, 2004), which have anti-inflammatory activities. Further studies will explore the effect of active components including cordycepin in Cordyceps militaris in acute colitis model.…”
Section: Discussionmentioning
confidence: 93%
“…Sustained high NO production in the colon plays a role in the pathology of IBD. Several studies have shown that CM extract suppresses iNOS expression and NO production in macrophages (Kim et al, 2006;Shin et al, 2009). The previous study demonstrated that the severity of DSSinduced colitis was significantly attenuated in iNOS knockout and in specific iNOS-inhibitor treated animals (Krieglstein et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the ratio of CD163 to CD68, the latter being a pan macrophage marker [45,46], was also greater in the PECUU group. M2 macrophages have been reported to produce TGF-β [47,48], which has been described as a multipotent cytokine with healing potential in various tissues by promoting cell growth and matrix accumulation, thus facilitating the ability of tissue to withstand stress without expanding [49]. Although the segregation of macrophages into two distinct phenotypes is a simplified framework of the in vivo reality, our findings may suggest that epicardial implantation of a patch with a moderate degradation rate has beneficial impact on infarct tissue healing through M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Cordycepin is extracted from fungi of genus Cordyceps, and has been used traditionally as an anti-tumor, anti-viral, anti-inflammatory agent in East Asian countries (21)(22)(23)(24)(25)(26). In this study, we examined the inhibitory effect of cordycepin on the melanogenesis signaling pathways, including the expression of MITF, tyrosinase, TRP1 and TRP2, and the phosphorylation of CREB, via the activation of ERK and Akt in murine B16F10 melanoma cells stimulated by α-MSH and IBMX.…”
Section: Introductionmentioning
confidence: 99%